Perancangan Enterprise Architecture Fungsi Marketing Dan Layanan Pelanggan Menggunakan Framework Togaf Adm Pada Pt. Herona Express - Ian Fahmi Nugraha; Yuli Adam Prasetyo; Basuki Rahmad (eProceedings of Engineering, 2016)
PT. Herona Express is a company in the delivery of services by rail and truck box but, in terms of information technology PT. Herona Express still less experienced competitors with other delivery services. In running the business activity of PT. Herona Express have a design enterprise architecture to support the process / business strategy. Business processes that are running the company is still done manually, such as marketing and customer service activities are still carried out manually. To provide the best service in the marketing and customer service, it is necessary to design Enterprise Architecture to illustrate the concept in the marketing and customer service. Based information systems strategic planning framework TOGAF ADM is one method that can be used to align business strategy and IT strategy. The results of this design in the form of a business model targets, and artifacts from each stage of the design include the Preliminary Phase through Technology Architecture and targeted solutions as outlined in the roadmap. Keyword : Enterprise Architecture, TOGAF ADM, PT. Herona Express, Information System Strategic Planning, Marketing, Customer Service.